Adsorption of Biologically Active Compounds from Aqueous Solutions on to Commercial Unmodified Activated Carbons. Part VI. The Mechanism of the Physical and Chemical Adsorption of Acetanilide - Artur P. Terzyk (Adsorption Science & Technology)
The new correlations recently suggested between the properties of the carbon surface and the constants characterizing the process of acetanilide adsorption were extended from data that had been measured initially for six carbons. It was shown that the mechanism of acetanilide adsorption on carbons was mixed between micropore filling and adsorption on active surface sites. The latter depended strongly on the concentration of surface carboxylic, phenol and basic groups. In acidic pH, the process was irreversible due to the chemisorption of acetanilide molecules on the nucleophilic carbon sites. The rate of adsorption of acetanilide increased at acidic pH levels. Diffusion was mainly a surface process with the energy of diffusion depending on the chemical composition of the carbon surface and its polarity.